Psychological well-being of health workers: the role of psychological contract breach and organizational citizenship behaviour (2011)
This research work is an exploratory study of Psychological Well-being among health workers in Ibadan. The main objective of the study was to assess some predictors of Psychological Well-being among health workers by considering the influence of psychological contract breach and Organizational Citizenship Behaviour. There were a total of 379 selected participants in the study. The Questionnaire used was a 51-item paper and pencil instrument having six sections. The instrument was content validated and each scale (section) had high reliability estimates. Scores obtained from the scales for Psychological contract breach and OCB were correlated with scores on the psychological well-being Scale using Pearson’s Product Moment Correlation. Multiple regression analysis was also run to determine their level of influence on psychological well-being. Findings in this study show that both Perceived Psychological Contract Breach and OCB had significant correlations with psychological well-being with the former being the most potent predictor of psychological wellbeing among health workers in Ibadan. Marital status and Age of the workers also had significant influence on Psychological Well-being. Implications of the results were discussed and suggestions were made towards improving quality of work among health workers in the society